Study of Hearing Status After Canal Wall Down Mastoidectomy with Type-III Tympanoplasty (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To observe hearing status in case of canal wall down mastoidectomy with type III tympanoplasty.Methods: This was a cross sectional study which was carried out in the departments of Otolaryngology and Head-Neck surgery of Bangabondhu Sheikh Mujib Medical University during the period of July’ 2011 to March’ 2012.A Total 38 patients having cholesteatoma underwent canal down mastoidectomy with type III tympanoplasty,were included in this study. Patients were divided into two groups according to their age. Age belonged to 18 years and more than 18 years were considered as child and adult respectively. Patients were examined thoroughly and preoperative hearing level was assessed by pure tone audiometry one one week before operation. Post operative patients were followed up at regular intervals. Pure tone audiogram (PTA) was done after 8 weeks and hearing assessment was compared by closure of air bone gap.Results: In this study majority of patients were within 13-17 years in child group and 18- 35years in adult group. Most of patients were male.Closure of air-bone gap was significantly higher in adults. Improvement of hearing status was more in adults.Conclusion: CWD mastoidectomy with tympanoplasty not only lowers recurrence rate but also improves hearing status although less likely in child and younger age group than adults.Bangladesh J Otorhinolaryngol; April 2017; 23(1): 52-58